دور المراجعة الداخلية في رفع كفاءة الأداء في الوحدات الحكومية: (( دراسة ميدانية على محليات ولاية النيل الأبيض)) ) خلال فترة 2004 م - 2014 م - د. احمد عبد الوهاب أبو محمد (White Nile Journal for Studies and Research, 2019)
The study aimed to identifying the role of internal audit in raising financial and administrative efficiency in the governorates of White Nile State during the period (2004-2014). The problem of the study was that the risks resulting from the failure of the internal auditor to provide adequate professional care and the threats of independence affect performance, led to the emergence of errors and irregularities. The study assumed that there is a scientifically qualified and professional cadre with expertise in internal auditing. The study used the deductive approach, by extrapolation of studies, research, books and periodicals, and the inductive method underlying the observation by addressing a number of laws governing the profession, The most important results are the presence of a scientifically qualified and professional cadre with experience that contributes to raising the efficiency of financial and administrative performance and its development, an effective system of internal control and continuous follow up contributes to raising the efficiency of performance. The study recommends removing the risks that threaten the independence of the internal auditor and the comprehensive review system, In non-audit areas as they contribute to the addition of value in government units.